An Evaluation of Mortality of Sitophilus Oryzae Treated with Selected Insecticides via Filter Paper and Food Impregnated Method - M. B, Ismeazilla; Z, Mohd Rasdi; O, Dzolkhifli; A, Norhayu; I, Izaitul Aida; K, Mohd Faizol; Z, Muhammad Shakir; A, Nur Fakriyah; S. M, Noor Shuhaina (Asian Journal of Agriculture and Rural Development, 2020)
Laboratory bioassay were conducted at University Putra Malaysia in order to evaluate the toxicity and the antifeedant activity of five insecticides which is Cypermethrin, Malathion, Prevathon, Rotenone and also Spinosad against the adult of S.oryzae by using the filter paper impregnation and food impregnation method for 1, 3, 5 and 7 days. Rotenone found to be effectives in toxicity via filter paper impregnation method based on the LC50 values with 0.003% while the other was 0.04%, 0.017%, 0.106% and 1.109% were indicated Spinosad, Malathion, Cypermethrin and Prevathon. The less effective was Prevathon. Food impregnation method showed that the effective insecticides was Spinosad with LC50 values 0.001%. The lowest was Prevathon with LC50 values 5.776%. In addition, the other insecticides showed LC50 values was 0.003%, 0.05% and 0.875% which indicated Malathion, Cypermethrin and Rotenone. For the antifeedant activity via feeding deterrent index (FDI), it showed that, the lowest FDI was Spinosad with 0.535% while the highest was Rotenone with 1.756%. The other showed 0.63%, 0.869% and 0.949% indicated Malathion, Cypermethrin and Prevathon respectively. As conclusion, most effective insecticides against adult of S.oryzae was Spinosad because able to control the insect at the prepared concentration in both method..